KATA KERJA BANTU MODALS DALAM NOVEL THE NOTEBOOK KARYA NICHOLAS SPARKS - KAMUH, CLAUDIA JENNIFER (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACTS Â In English there are two subclasses of verbs, those are lexical verb and auxiliary verb. Modals are a class of auxiliary verbs that are combined with the basic form to make verb phrase with a wide meaning. The study is an attempt to describe and analyze the modals in the novel â€œThe Notebookâ€ by Nicholas Sparks. The aim of this research is to identify and classify the form and meaning of modals. The method used in this research is descriptive method. The data of modals have been taken from the sentences in the novel â€œThe Notebookâ€ and analyzed by using Azarâ€Ÿs concept. The result of this study shows that pure modals forms which used namely Can, Could, Will, Would, Should, May, Might, Must. Special modals forms which are namely Have to. Semi modals which are namely Used to. The most frequently appear modals in the article is Would. This study can be continually done by analyzing modals in another literary works by using the concept of Azar. Â Keywords: Modals, English, Novel â€œThe Notebookâ€